The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1029/jb081i002p00297
|View full text |Cite
|
Sign up to set email alerts
|

Fault motion in the larger earthquakes of the Kurile-Kamchatka Arc and of the Kurile-Hokkaido corner

Abstract: The focal mechanisms of 120 larger earthquakes (mb ≥ 5.7) of the Kurile‐Kamchatka arc for the period 1962–1973 illustrate particular features of the subduction of the Pacific plate beneath this island arc system. The faulting characteristic of normal‐depth earthquakes is consistent with convergence of the oceanic plate in the direction N60°W with respect to the continental plate. Shallower foci under the trench are tensional; those seaward of the trench and related to the Hokkaido rise are compressional. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…36 in Table 1), a good agreement between the solutions determined by these authors and those determined in the present study was obtained. The solutions for earthquake 36 determined by STAUDER and MUALCHIN (1976) and in the present study are shown in Fig. 6(c).…”
Section: Focal Mechanismmentioning
confidence: 97%
See 4 more Smart Citations
“…36 in Table 1), a good agreement between the solutions determined by these authors and those determined in the present study was obtained. The solutions for earthquake 36 determined by STAUDER and MUALCHIN (1976) and in the present study are shown in Fig. 6(c).…”
Section: Focal Mechanismmentioning
confidence: 97%
“…These solutions have also been determined by ISACKS andMOLNAR (1971) andMUALCHIN (1976). Except Table 1.…”
Section: Focal Mechanismmentioning
confidence: 99%
See 3 more Smart Citations